SOME BIOLOGICAL CHARACTERISTIC OF SILVER RED SNAPPER CATCHED IN THE SEA WATERS OF NHA TRANG- KHANH HOA - Mao, Nguyen Dinh; Thanh, Nguyen Dich (Vietnam Journal of Marine Science and Technology, 2008)
This paper presents some main results of study on the biology for Silver red snapper  (Lutjanus argentimaculatus Forskal, 1775) in the seawaters  of Nha Trang - Khanh Hoa during 2005 - 2006. The study is concluded that the minimum size of female  Lutjanus argentimaculatus at maturity is 48 cm (3 age), and that the spawning may occur at fish size of 48 - 76 cm. The fecundity of female is variable in fish size or age groups: the number of ova at the length of 4 age is 895 × 103, 5 age is 995 × 103 and 6 age is 4,1 × 106 ova. The sex ratio of L. argenlimaculatus in general that on young,  immature fishes have the ratio dominated by males, whereas those that capture  mostly older and spaning age fishes have sex rutios that are mostly females.